HUMAN PAPILLOMA VIRUS (HPV) AS A POTENTIAL CO-FACTOR IN BREAST CANCER - A RETROSPECTIVE CASE-CONTROL STUDY (Applied Biological Research, 2026)
Human papillomavirus (HPV) is an increasingly debated etiological factor in breast cancer, with growing evidence suggesting its potential role as an early trigger in breast carcinogenesis. This retrospective case–control study investigated the prevalence and genotypic distribution of HPV DNA in breast carcinoma tissues compared with non-malignant breast tissues to evaluate a possible association between HPV infection and breast cancer. The study was conducted from 1 January 2024 to 15 March 2025 and included 230 formalin-fixed paraffin-embedded (FFPE) breast tissue specimens collected from Azadi Teaching Hospital, Kirkuk General Hospital, and private laboratories in Kirkuk city, Iraq. Among these, 130 samples were diagnosed as breast cancer cases, while 100 samples represented benign breast lesions as controls. Clinical and pathological data—including tumour grade, tumour stage, estrogen receptor (ER), progesterone receptor (PR), and HER-2/neu status—were obtained from medical records. Molecular detection of HPV was performed using High- and Low-Risk PapillomaStrip assays and polymerase chain reaction (PCR). HPV DNA was detected at a significantly higher frequency in breast cancer tissues than in controls (P < 0.0001). HPV type 32 was the most prevalent genotype, identified in 24.6% of breast cancer samples compared to 3% of control samples. HPV positivity was predominantly observed in high-grade (grade III) and advanced-stage tumours. No significant association was found between HPV positivity and tumour laterality, ER status, or PR status. However, HPV-positive cases demonstrated a significantly higher proportion of HER-2 positivity than HPV-negative cases. In conclusion, HPV infection was more prevalent among breast cancer patients, particularly in HER-2–positive, high-grade, and advanced-stage tumours, suggesting a potential role of HPV in aggressive breast cancer progression.
Keywords: Breast cancer; hormone receptor status; human papilloma virus; molecular detection